POLA MORFOLOGIS AFIKSASI KE-AN DALAM BAHASA INDONESIA: PENDEKATAN MORFOLOGI - Angelita, Tasya; Sawardi, F.X.; Sumarlam (IAIN Surakarta, 2025)
This study examines the affixation of ke-an in non-standard Indonesian from a derivational and inflectional perspective. This study was a descriptive qualitative method with data sources taken from the Telegram accounts named Yuenes Fess and Yuenes Friends. The data analysis techniques were the distribution method, the BUL (Divide Direct Elements) technique, and advanced techniques in the form of expansion and replacement techniques. The BUL technique divided the lingual unit of data into several elements, which are the parts that directly form the lingual unit in question. The results showed that the affix ke-an is one of the productive affixes in non-standard Indonesian, especially as a word builder with the verb category. The affix ke-an can cause changes in lexical identity and shifts in meaning in the process of derivational morphology. This study also found that the use of the affix ke-an in non-standard Indonesian can differ from the use of the affix ke-an in standard Indonesian. All basic forms experience changes in category and identity. This results in changes in word meaning, giving rise to several noun meanings.Keywords: affixation ke-an, derivational, inflectional, morphology, non-standard Indonesian